2010
DOI: 10.1111/j.1365-2869.2010.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of sleep duration with sociodemographic and health-related factors, psychiatric disorders and sleep disturbances in a community sample of Korean adults

Abstract: Summary The aim of this study is to examine relationships of sleep duration with sociodemographic and health‐related factors, psychiatric disorders and sleep disturbances in a nationwide sample in Korea. A total of 6510 subjects aged 18–64 years participated in this study. Logistic regression was used to calculate the odd ratios and 95% confidence intervals of the covariates, psychiatric disorders and sleep disturbances across the following sleep duration categories: 5 h or less, 6, 7, 8 and 9 h or more per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
84
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 40 publications
(91 reference statements)
14
84
5
3
Order By: Relevance
“…This is not in agreement to what was reported by This current study has shown that there was a significant difference between Apgar scores of the babies at one minute after birth and the mothers' actual night sleep duration. There is also a highly significant difference between the baby's Apgar score of five minutes after birth (Park et al, 2010). In the present study, birth weight was related to labor outcomes; there was a highly significant difference between birth weight and duration of sleep at night.…”
Section: Discussionmentioning
confidence: 51%
“…This is not in agreement to what was reported by This current study has shown that there was a significant difference between Apgar scores of the babies at one minute after birth and the mothers' actual night sleep duration. There is also a highly significant difference between the baby's Apgar score of five minutes after birth (Park et al, 2010). In the present study, birth weight was related to labor outcomes; there was a highly significant difference between birth weight and duration of sleep at night.…”
Section: Discussionmentioning
confidence: 51%
“…Although short sleep duration can be voluntarily induced as in BISS, sleep duration may also be shortened despite efforts to sleep as in adolescent insomnia or depression. 4,5 A "natural" short sleeper without BISS may sleep less without voluntary effort to curtail sleep. In addition, the correlation between subjective measurement of sleepiness as ESS and objective of sleepiness as multiple sleep latency test (MSLT) has been reported not to be as high as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents experiencing insomnia 4 or depression 5,6 may be unable to get suffi cient sleep despite efforts to do. Because there are large individual variations in sleep need, a typically short sleeper can sleep less without sleep debt or sleepiness than ordinary people.…”
mentioning
confidence: 99%
“…Chronic diseases cause more than 50% of deaths worldwide [1,2]. Furthermore, it is estimated that deaths from chronic diseases will increase by 15% in the next 10 years [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is estimated that deaths from chronic diseases will increase by 15% in the next 10 years [1][2][3][4]. Mood and Anxiety disorders have highly prevalent conditions in diabetes and have a significant impact on health outcomes [5,6].…”
Section: Introductionmentioning
confidence: 99%